2007
DOI: 10.1038/sj.cdd.4402229
|View full text |Cite
|
Sign up to set email alerts
|

The shadow of death on the MET tyrosine kinase receptor

Abstract: The MET tyrosine kinase receptor is a high-affinity receptor for hepatocyte growth factor/scatter factor (HGF/SF). HGF/SF-MET system is necessary for embryonic development, and aberrant MET signalling favours tumorigenesis and metastasis. MET is a prototype of tyrosine kinase receptor, which is able to counteract apoptosis through the initiation of a survival signal involving notably the PI3K-Akt pathway. Paradoxically, the MET receptor is also able to promote apoptosis when activated by HGF/SF or independentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 97 publications
(89 reference statements)
1
57
0
Order By: Relevance
“…We noted an increased association between CD44v6 and c-Src in ASML cells, which was accompanied by increased activation of the focal adhesion kinase, 5 which can trigger PI3K activation. It also has been described that c-met supports tumor cell survival via PI3K/Akt activation (45,46) and that c-met interacts with CD44v6 via hepatocyte growth factor/scatter factor binding (23). Notably, c-met activity is significantly reduced in ASML-CD44v kd cells.…”
Section: Cd44v and Apoptosis Protectionmentioning
confidence: 87%
“…We noted an increased association between CD44v6 and c-Src in ASML cells, which was accompanied by increased activation of the focal adhesion kinase, 5 which can trigger PI3K activation. It also has been described that c-met supports tumor cell survival via PI3K/Akt activation (45,46) and that c-met interacts with CD44v6 via hepatocyte growth factor/scatter factor binding (23). Notably, c-met activity is significantly reduced in ASML-CD44v kd cells.…”
Section: Cd44v and Apoptosis Protectionmentioning
confidence: 87%
“…We have previously demonstrated that Met is cleaved by caspases, which separate the extracellular ligand-binding domain from the intracellular kinase domain. In addition to abolishing the ligand responsiveness of Met, these cleavages generate a cytoplasmic proapoptotic fragment named p40 Met, involved in apoptosis amplification (Tulasne et al, 2004;Foveau et al, 2007;Deheuninck et al, 2008;Tulasne and Foveau, 2008). Many other fragments of Met have been described, but their biological functions, and the mechanisms involved in their generation have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…HGF binding results in receptor dimerization, activation, and internalization mediated by the phosphorylation of multiple tyrosine residues in the MET intracellular domain (1)(2)(3)(4)(5)(6). Signaling through MET results in cell survival, proliferation, motility, migration, and complex morphogenetic processes (2,7,8). Although MET signaling is essential for embryonic development and tissue repair in adults (2), aberrant signaling through activating MET mutations (3,4,8), MET overexpression (9,10), or dysregulated autocrine expression of HGF and MET in tumor cells (9)(10)(11)(12)(13) contributes to malignant progression and metastasis of cancer cells (2,7,8).…”
Section: Introductionmentioning
confidence: 99%